2015
DOI: 10.2147/ott.s85899
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of protein tyrosine phosphatase 4A2 in breast cancer

Abstract: Abstract:Although PTP4A3 has been shown to be a very important factor in promoting cancer progression, the role of its close family member PTP4A2 is still largely unknown. Recent reports have shown contradicting results on the role of PTP4A2 in breast cancer progression. Considering this, we aimed to investigate the prognostic value of PTP4A2 in five independent breast cancer data sets (minimum 198 patients per cohort, totaling 1,124 patients) in the Gene Expression Omnibus Database. We found that high express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…Therefore, it will be meaningful to nd new biomarkers that can provide additional staging information to help select treatments and optimize treatment outcomes. Recent studies have noted that the expression of PTP4A2 is upregulated in several cancer types such as breast, colon and pancreatic cancer [19,20,21]. Consistent with these studies, we reported for the rst time that PTP4A2 expression was markedly upregulated in HCC tissues.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Therefore, it will be meaningful to nd new biomarkers that can provide additional staging information to help select treatments and optimize treatment outcomes. Recent studies have noted that the expression of PTP4A2 is upregulated in several cancer types such as breast, colon and pancreatic cancer [19,20,21]. Consistent with these studies, we reported for the rst time that PTP4A2 expression was markedly upregulated in HCC tissues.…”
Section: Discussionsupporting
confidence: 90%
“…These data indicate that PTP4A2 can indirectly regulate the transcription level of RAB24. Histone modi cation is an important epigenetic mechanism that regulates gene expression (eg: histone acetylation and/or methylation), and plays an important role in cancer genesis [20,21]. Next, we explored whether histone acetylation or methylation status were affects by PTP4A2 in RAB24 promoter.…”
Section: Ptp4a2 Promotes Hdac1 Accumulation In the Cytoplasm Of Hcc Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we identified a novel circRNA hsa_circ_0007364, derived from RNA cyclization following a head-to-tail splicing of exon 2 and exon 3 of PTP4A2 (protein tyrosine phosphatase 4A2). PTP4A2 has been reported to influence tumor progression and stem cell self-renewal [ 25–27 ]. Here, we found that hsa_circ_0007364 is remarkably overexpressed and correlates with advanced FIGO stage and lymph-node metastasis in CC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the PRL family, PRL2 is the least studied member. While studies have reported that PRL2 is overexpressed in pancreatic, breast and lung cancer samples and its level is associated with tumor progression, there is still a lack of information available regarding the function of PRL2 ( 12 ). The expression of PRL2 is the most abundant of the three PRLs and PRL2 mRNA is almost ubiquitously expressed at high levels in normal adult human immune tissues, suggesting that PRL2 may have a specific role in immune function ( 13 ).…”
Section: Introductionmentioning
confidence: 99%